Adsorption behaviour of copper onto a novel modified chitosan material: thermodynamic study. Issue 52 (7th November 2016) - Flores-Alamo, N.; Gómez-Espinosa, R.M.; Solache-Ríos, M.; García-Rivas, J.L.; Zavala-Arce, R.E.; García-Gaitán, B.
Abstract: The adsorption behaviour of Cu(II) was investigated in the presence of a new material. This material was obtained from chitosan (Ch) and polyvinyl alcohol (PVA) at different weight percentages (35/65, 50/50 and 65/35), dripping this mixture in a NaOH solution, and then subjecting to crosslinking reaction under nitrogen atmosphere at 353 K with ethylene glycol diglycidyl ether to improve its resistance to acids and alkalis. Adsorption test were conducted to evaluate the optimal Ch/PVA ratio, 35/65 ratio presented the best adsorption capacity. The interaction between Cu(II) and functional groups of Ch/PVA was determined by Fourier transformed infrared spectroscopy. Kinetics and isotherm experiments were performed to evaluate the adsorption behaviour of Cu(II). The kinetic experimental data were best fitted to pseudo-second-order model and equilibrium data to the Langmuir model. Thermodynamics parameters such as free Gibbs energy (Δ G °), enthalpy (Δ H °) and entropy (Δ S °) were calculated. These parameters indicated spontaneous and endothermic adsorption process.